Efektivitas Implementasi Kurikulum Merdeka di Sekolah Penggerak PAUD Al Fatih Kota Lubuklinggau - Putra, Mansyur Romadon (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to determine the effectiveness of the implementation of the Independent Curriculum at the Al Fatih Early Childhood Education Driving School, Lubuklinggau City. The Merdeka Curriculum is designed to provide flexibility to educators in adapting the learning process to children's needs and interests. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of the Independent Curriculum at PAUD Al Fatih is quite effective, shown by increasing children's active participation in learning activities, teachers' creativity in compiling teaching modules, and school management support in providing appropriate learning facilities. However, there are still several challenges such as limited training for teachers and the need to strengthen the understanding of the curriculum as a whole. This study recommends increasing continuous training and mentoring for educators to maximize the implementation of the Independent Curriculum in the PAUD environment.